2019
DOI: 10.1101/759241
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Growth-regulated Hsp70 phosphorylation regulates stress responses and prion maintenance

Abstract: Maintenance of protein homeostasis in eukaryotes during normal growth and stress conditions requires the functions of Hsp70 chaperones and associated co-chaperones.Here we investigate an evolutionarily-conserved serine phosphorylation that occurs at the site of communication between the nucleotide-binding and substrate-binding domains of Hsp70. Ser151 phosphorylation in yeast Hsp70 (Ssa1) is promoted by cyclindependent kinase (Cdk1) during normal growth and dramatically affects heat shock responses, a function… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 95 publications
(119 reference statements)
0
0
0
Order By: Relevance
“…HSP70 multi-domain protein levels were very low in the mycelia of S. bambusicola but significantly increased during conidial formation. As a non-specific protective protein, HSP70 can help denatured proteins restore their correct conformation, facilitate the folding and assembly process of nascent peptide chains, and significantly improve the resistance of cells to stress (Kao et al, 2020). The differential proteins were also concentrated in the endocytic patch.…”
Section: Discussionmentioning
confidence: 99%
“…HSP70 multi-domain protein levels were very low in the mycelia of S. bambusicola but significantly increased during conidial formation. As a non-specific protective protein, HSP70 can help denatured proteins restore their correct conformation, facilitate the folding and assembly process of nascent peptide chains, and significantly improve the resistance of cells to stress (Kao et al, 2020). The differential proteins were also concentrated in the endocytic patch.…”
Section: Discussionmentioning
confidence: 99%
“…Although the activity of Hsp70 is firstly dependent on its expression, some enzymes also may introduce modifications, regulating Hsp70 in kinase dependent manner. For instance, it has been reported that cyclin-dependent kinase 1 (Cdk1) is able to temporarily downregulate chaperonic functions of Hsp70 by phosphorylation of serine in a region between ATP-and substrate-binding domains (Kao et al, 2020). Interestingly, in addition to de novo synthesis of Hsp70, neurons tend to uptake it from neighboring astrocytes (Tytell et al, 1986;Hightower and Guidon, 1989;Guzhova et al, 1998Guzhova et al, , 2001Kalmar and Greensmith, 2017).…”
Section: Cellular Regulation Of Hsp70mentioning
confidence: 99%